Healthcare needs and risk in police custody - Thorley, Grace M. (2017)
Police custody is an area of scholarly research that has previously been overlooked. Whilst the research and literature regarding this topic begins to grow, there still remains a wide variety of aspects to be considered. Chapter One presents a general introduction to the topic. Chapter Two presents a literature review following a systematic approach regarding the healthcare needs of those detained in police custody. The findings revealed that there is a considerable presence of mental health, substance misuse, and physical health care needs amongst police custody detainees. Chapter Three presents a critique of an impulsivity measure, the Barratt Impulsiveness Scale (BIS-11). The concluding remarks reported that further research is essential in examining the psychometric properties amongst forensic populations. The indications regarding reliability and validity are supportive, although further evidence considering the effectiveness of this tool for decision-making would be beneficial. Chapter Four, an empirical study, examined the prevalence of impulsivity, self-harm, and situational aggression amongst detainees. In addition, the predictive validity of one of the National Strategy for Police Information Systems (NSPIS) risk assessment was reviewed. This study identified that impulsivity traits are highly prevalent amongst detainees (for the non-planning impulsiveness subtrait); for self-harmers, their function of this behaviour was identified as ‘self-punishment’; and 40% engaged in some form of aggressive behaviour throughout their detention. The NSPIS risk assessment has significant predictive value, although with the additional of one Dynamic Appraisal of Situational Aggression (DASA) assessment and the BIS-11 total score, the predictability increases by 21%. A single case study in Chapter Five considers the effectiveness of Dialectical Behaviour Therapy (DBT)-informed skills training in the community. This individual displayed borderline personality disorder traits and exhibited self-harming behaviours. The difficulties associated with working with such a client group have been discussed. In Chapter Six, a discussion concludes the thesis.